2020
DOI: 10.1186/s12885-020-06977-0
|View full text |Cite
|
Sign up to set email alerts
|

Elderly women’s experiences of self-sampling for HPV testing

Abstract: Background: Self-sampling for HPV testing, as an alternative to the conventional speculum based sampling, is highly acceptable to women of screening ages. The aim of this study was to describe older women's (60 to 75 years) experiences of self-sampling. Methods: In Sweden a descriptive study with quantitative and qualitative methods was designed to collect data from a survey of women who participated in self-sampling for HPV testing. Individual interviews were done with women who tested positive in the first s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Acceptability of the self-sampling HPV test was favorable. This result is consistent with many previous studies across various countries [ 7 , 22 28 ]. In contrast to the overall favorable acceptability of the test, concerns about the self-sampling procedures were recognized.…”
Section: Discussionsupporting
confidence: 94%
“…Acceptability of the self-sampling HPV test was favorable. This result is consistent with many previous studies across various countries [ 7 , 22 28 ]. In contrast to the overall favorable acceptability of the test, concerns about the self-sampling procedures were recognized.…”
Section: Discussionsupporting
confidence: 94%
“…Cancer Month 0, 2020 populations, reducing the embarrassment that often accompanies these tests in a medical office. [23][24][25][26][27] There are cost differences, however. Cologuard has a lower cost per screening than colonoscopy, but the screening intervals are more frequent, and therefore the overall cost per patient is higher.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the evidence for mt‐sDNA testing and FIT, and the emerging findings regarding cervical self‐screening, home‐based patient screening is both accessible and acceptable to patients 18‐22 across diverse populations, reducing the embarrassment that often accompanies these tests in a medical office 23‐27 . There are cost differences, however.…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating the experiences of self-testing at home in older participants (60 to 75 years of age) in Sweden, the majority of participants found self-sampling to be easy or very easy to perform and preferred self-sampling over clinician-collected sampling. 40 The authors found that participants who had more understanding about HPV infection and its relationship to cervical cancer were more concerned about receiving a positive HPV test result. 40 Other studies have found generational differences and report that self-sampling is generally more acceptable to younger individuals.…”
Section: Transgender or Non-binary Individualsmentioning
confidence: 99%
“…40 The authors found that participants who had more understanding about HPV infection and its relationship to cervical cancer were more concerned about receiving a positive HPV test result. 40 Other studies have found generational differences and report that self-sampling is generally more acceptable to younger individuals. 33,41 Medically Underserved Populations…”
Section: Transgender or Non-binary Individualsmentioning
confidence: 99%